Single‐Crystal X‐ray Diffraction and Solution Studies of Anion–π Interactions in N‐(Pentafluorobenzyl)pyridinium Salts. Issue 12 (17th January 2014) - Giese, Michael; Albrecht, Markus; Repenko, Tatjana; Sackmann, Johannes; Valkonen, Arto; Rissanen, Kari
Abstract: A solid‐state structural study on anion–π interaction in various N ‐(pentafluorobenzyl)pyridinium salts accompanied by NMR spectroscopic investigations is presented. The crystal structures of1a –1d reveal different kinds of contacts with anions, including anion–π interactions. In particular, the solid‐state structure of1b ‐I3 shows distinct evidence of anion–π interactions. Attempts to study anion–π interactions in solution were not successful, but their presence in solution could not be ruled out. Abstract : The interactions of N ‐(pentafluorobenzyl)pyridinium salts are investigated in the solid state as well as in solution. The triiodide salt shows distinct evidence of anion–π interactions with both the pyridinium and the pentafluorophenyl unit. Solution investigations to prove the attractive nature of the noncovalent force failed, but they did not rule out the presence of the interaction.